Speech Act Analysis in Social Interactions of Adolescents in Tapak Suci Training at Muhammadiyah Bangkalan - Muhammad Irwan Ardiansyah (Journal of Social, Culture, and Language, 2026)
Language is the primary medium for humans to communicate and interact in social life. In pragmatic studies, language is not merely a tool for transmitting information but also a means of performing actions. This concept is reflected in the theory of speech acts introduced by Austin (1962) and later developed by Searle (1969). This research examines adolescents’ speech acts during Tapak Suci martial arts training within the Muhammadiyah Bangkalan community. The purpose of this study is to describe the forms and functions of speech acts used during training sessions and to analyze the role of language as a medium for shaping discipline, motivation, and social solidarity. This study employs a descriptive qualitative method using observation, recording, and note-taking techniques. The data were analyzed based on George Yule’s (1996) theory of speech acts, which classifies them into three categories: locutionary, illocutionary, and perlocutionary acts. The findings reveal four main types of speech acts—directive, expressive, commissive, and declarative. Directive acts are used to give instructions, expressive acts to convey emotions, commissive acts to show commitment, and declarative acts to establish rules or group values. The results demonstrate that communication during Tapak Suci training serves not only a technical purpose but also functions as a means of character building, discipline formation, and social solidarity among members. Thus, speech acts reflect the social and religious values embedded in the moral development of Muhammadiyah adolescents in Bangkalan. Keywords: speech acts, pragmatics, adolescents, Tapak Suci, social interaction